Role of working capital management in profitability considering the connection between accounting and finance - Amer Morshed (Emerald Publishing Limited, 2020)
The study aims to explain the relationship between accounting and finance through measuring the effect of rational working capital management on profitability.Employing the methodology of semi-structured interviews with sixteen financial managers.The findings pointed out the relationship between accounting and finance is complementary, since it supports the accountant by the critical skills and information, like project evaluation, managing the company funding resources and working capital management. These skills put the accountant up to the financial manager stage. The working capital investment and financing policies have the most significant impact on profitability. These policies related to risk and return theory; since the conservative policy will reduce both the risk and return and the aggressive one will have the opposite impact.It recommends accountants to be in professional stage and increase the profitability of the company to grab both accounting and finance information and skills.